Pengembangan Decission Support System dengan Metode SAW dan AHP guna menentukan Dosen Berprestasi - Siddiq, Miftahussa'adah Putri; Wirani, Yekti (DBESTI: Journal of Digital Business and Technology Innovation, 2024)
Determination of Outstanding Lecturers is part of the LPPM Research Award program initiated by LPPM STT Terpadu Nurul Fikri. The LPPM Research Award is an activity to give achievement to Lecturers at STT Terpadu Nurul Fikri who have conducted research and community service while serving as teaching staff at STT Terpadu Nurul Fikri. The LPPM Research Award is one of the work programs in the Annual Activity Implementation Plan and Budget (RPKAT), which the Integrated LPPM STT Nurul Fikri must carry out. The LPPM STT Terpadu Nurul Fikri is still having difficulties realizing the program because of obstacles in processing data and determining lecturers who get awards. This is due to many lecturers and their track record of research and community service. The purpose of this study was to find out what categories and standard criteria were used in the LPPM Research Award and to produce a list of lecturers who won the LPPM Research Award. The scope used in this research is to use the AHP and SAW methods, the data to be used from 2019-2020, and the final result in the form of a list of lecturers displayed via Google Spreadsheet.